The best parameters selection using pso algorithm to solving for ito system by new iterative technique - Karam Adel Abed; Abeer Abdulkhaleq Ahmad (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The main aim of this study is to obtain the best approximate solution for the nonlinear Ito system by applying the new iterative method, A new technique has been proposed that combines the new iterative method with the particle optimization algorithm. The most important distinctive of this work is the analysis of errors between the exact solution of the system and the approximate solutions, which showed us that these approximate solutions of the proposed technique in particular have high accuracy because they converge significantly from the exact solution.